AN ANALYSIS OF POLITENESS STRATEGIES USED BY TWO SPEAKERS ON INTERNATIONAL LANGUAGE EDUCATION CONFERENCE - Salsabila, Zahra Muthia; Yugafiati, Rasi; Anggraeni, Anita (PROJECT (Professional Journal of English Education), 2024)
Politeness strategies is a branch of pragmatic. When people interact and communicate, they should know how to respond to the answer or topic to lead a pleasant conversation with the right strategy. The purpose of this study is to examine how two presenters on an international webinar employed four different sorts of politeness strategies: off-record politeness, bald-on-record, positive politeness and negative politeness. The researcher also intends to examine the dominant strategy employed there. In this study, the qualitative descriptive method was used. The information was obtained via recording of an international webinar. The data was analyzed using Brown and Levinson's (1987) theoretical framework. Following analysis, the findings showed that both speakers only employed the three politeness methods of negative politeness, positive politeness and off-record politeness. Both speakers do not employ "bald on-record" because it is used by persons with close relationships. The first speaker utilized 57 strategies in total. The second speaker uses 46 different politeness strategies in total. Positive politeness is a dominant strategy that is used by two speakers while delivering their material on international webinar. The importance of this research is to understand the message communicated by speakers when delivering their material.